2020
DOI: 10.1186/s12890-020-1099-9
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical impairment of dynamic left ventricular systolic and diastolic function in patients with obstructive sleep apnea and preserved left ventricular ejection fraction

Abstract: Background: Hypoxia affects myocardial oxygen supply resulting in subclinical cardiac dysfunction in obstructive sleep apnea (OSA) patients, with cardiovascular complications being associated with increased oxidative burst (OB). The aims of our study were to assess left ventricular (LV) dynamic myocardial deformation and diastolic reserve at rest and upon exercise, along with OB determination in this patients subset. Methods: Conventional echocardiography, Doppler myocardial imaging and LV 2D speckle tracking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
1
3
0
2
Order By: Relevance
“…As a result of inadequate compression and twisting of extracellular matrix during the systole, the loss of LV suction can induce abnormal relaxation and impaired diastolic function [ 39 ]. The value of e’ was independently associated with GWI in our study, which corroborates previous research [ 40 ]. The significant contribution of deformation in the calculation of MW may explain the independent associations between GLS and MW indices in our study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…As a result of inadequate compression and twisting of extracellular matrix during the systole, the loss of LV suction can induce abnormal relaxation and impaired diastolic function [ 39 ]. The value of e’ was independently associated with GWI in our study, which corroborates previous research [ 40 ]. The significant contribution of deformation in the calculation of MW may explain the independent associations between GLS and MW indices in our study [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Отношението Е/е' също се променя сигнификантно при двете групи пациенти при физическо натоварване, като то се асоциира силно с нарушена диастолна функция, превалираща в групата с ОСА. Изводът от това е, че пациентите с ОСА макар и клинично без симптоматика са със значително по-нарушена диастолна дисфункция в сравнение с пациенти без ОСА [7].…”
Section: терапияunclassified
“…ОСА се характеризира с повтарящи се и продължаващи повече от 10 секунди прекъсвания (апнеи) или намаляване (хипопнея) на дихателния поток с над 50% за повече от 10 секунди по време на сън и десатурация ≥ 4%, дължащи се на обструкция на горните дихателни пътища [7].…”
unclassified
“…A limited number of small studies have consistently reported that patients with moderate-to-severe degree of OSA have a higher prevalence of left ventricular diastolic dysfunction (LVDD) 13–21. LVDD is the impairment of the relaxation ability of the myocardium and the impairment of the LV to fill appropriately without increasing filling pressures 22 23.…”
Section: Introductionmentioning
confidence: 99%